2012
DOI: 10.1002/jssc.201200010
|View full text |Cite
|
Sign up to set email alerts
|

A novel strategy for target profiling analysis of bioactive phenylethanoid glycosides in Plantago medicinal plants using ultra‐performance liquid chromatography coupled with tandem quadrupole mass spectrometry

Abstract: Phenylethanoid glycosides are a group of phenolic compounds with diverse biological activities such as hypotensive, diuretic, and hypoglycemic effects. In this study, a target profiling analysis approach using ultra-performance liquid chromatography coupled with tandem quadrupole mass spectrometry (MS) was established on the basis of parent ion scanning for m/z 161, the characteristic product ion for phenylethanoid glycosides. It was successfully employed to discriminate the chemical composition of phenylethan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 37 publications
(43 reference statements)
4
39
1
Order By: Relevance
“…Other lesser used techniques for detection of plantamajoside are capillary electrophoresis (CE) (Gonda et al, 2013), ultraperformance liquid chromatography (UPLC)-MS/MS (Qi et al, 2012), ultra-performance liquid chromatography (UPLC)-UV (Zhou et al, 2013), high performance centrifugal partition chromatography (HPCPC)-electrospray ionization multi stage tandem mass spectrometry (ESI-MS) the negative ion mode (Li et al, 2008), (HPCPC)-HPLC (Li et al, 2009), spectrophotometry (Murai et al, 2009a), NMR spectroscopy (Rønsted et al, 2000) and liquid chromatography (LC)-combined with mass spectroscopy (MS)/MS .…”
Section: Analytical Methods and Techniques For Determination Of Plantmentioning
confidence: 99%
See 1 more Smart Citation
“…Other lesser used techniques for detection of plantamajoside are capillary electrophoresis (CE) (Gonda et al, 2013), ultraperformance liquid chromatography (UPLC)-MS/MS (Qi et al, 2012), ultra-performance liquid chromatography (UPLC)-UV (Zhou et al, 2013), high performance centrifugal partition chromatography (HPCPC)-electrospray ionization multi stage tandem mass spectrometry (ESI-MS) the negative ion mode (Li et al, 2008), (HPCPC)-HPLC (Li et al, 2009), spectrophotometry (Murai et al, 2009a), NMR spectroscopy (Rønsted et al, 2000) and liquid chromatography (LC)-combined with mass spectroscopy (MS)/MS .…”
Section: Analytical Methods and Techniques For Determination Of Plantmentioning
confidence: 99%
“…With respect to the chemical structure and bioactivity of the of the polyphenolic glycoside compounds, Qi et al (2012) suggested that the difference between verbascoside containing a glucose and a rhamnose, and plantamajoside with two glucose moieties were likely to account for the differences in diuretic or hypotensive effects of extracts of plant drugs as Plantaginis Herba and Plantaginis Semen. In contrast to the antiproliferative activity, the sugar groups may have a certain influence on hypotensive effects (Mølgaard, 1992;Qi et al, 2012).…”
Section: Bioactivities Of Plantamajosidementioning
confidence: 98%
“…Acteoside (1), plantamajoside (2), isoacteoside (3), isoplantamajoside (4), desrhamnosylverbascoside, rehmannioside and many others are representative phenylethanoid glycosides isolated from Cheqian [4,5]. Some of them are shown in Fig.…”
Section: Phenylethanoid Glycosidesmentioning
confidence: 99%
“…Putative identification was carried out using detailed study of the fragmentation patterns of the two authentic standards plantamajoside and acteoside, application to the similar PGs, and consulting the scientific literature. Fragmentation patterns of most PGs also present in these samples are described in , Petreska et al, 2011and Qi et al, 2012and Shi et al (2013. For practical reasons and to show the "taxonomy" of the detected molecules and fragments, the abbreviations of the PG subunits (glucose (Glc), caffeic acid (CA), hydroxytyrosol (HT), etc.)…”
Section: Phenylethanoid Glycosides In P Lanceolata Callimentioning
confidence: 99%
“…Chief fragmentation patterns of PGs were evaluated on basis of , Petreska et al, 2011and Qi et al, 2012and Shi et al (2013. Frequently found fragments and neutral loss values were interpreted by literature review and comparison with chief fragmentation routes of our standards (acteoside and plantamajoside).…”
Section: Identification Of Pgsmentioning
confidence: 99%